Communicating Home During the COVID-19 Pandemic: Lessons Learned from a Middle Grades Speech Therapist - Kelsey Jenkeleit (Middle Grades Review, 2022)
The COVID-19 pandemic changed how communication occurred between parents and teachers. This autoethnography focuses on my experiences as a middle grades speech therapist during the 2020-2021 school year, with a specific focus on parent-teacher communication. Using a Funds of Knowledge framework to help me analyze, understand, and describe communication data gathered over the course of the pandemic, I found that (1) communication increased during remote learning as more parents were home with their children; (2) the folding of work and home presented unique communication challenges, and (3) I felt a yearning for more communication to continue, especially after students returned to school. Future research possibilities include finding if virtual communication methods continue beyond the pandemic and understand how and why communication might continue to change and develop.
Keywords: parent-teacher communication; middle grades; special education; speech therapy